Use of technical communication prepared by science and engineering consultants - Fultz, Aaron S. (University of Wisconsin--Stout, 2018)
The key objectives of this study are to identify how clients of a global science and engineering firm use the technical communication they receive from the consultancy and to determine how closely that use matches the expectations of the consultants who develop and deliver the communication. More specifically, the research attempts to ascertain the types and frequency of technical communication received by the clients, what they generally consider most important within the communication, how they transfer (parse, repurpose, and/or share) the communication, and how often they look at and transfer such communication. In turn, the science and engineering consultants were asked their understanding of how clients might respond to the preceding inquiry. The answers from clients and consultants are then compared to identify gaps or deficiencies in the consultants' understanding of what modes of communication delivery work best for clients, or are at least which are preferred, and how technical communication developed by the science and engineering consultants can be altered to better meet client needs.
Keywords: Communication of technical information; Consultants